Acoustic and Electromagnetic Waves - Jones, D. S. (New York, NY Oxford University Press, 1986)
From a mathematical point of view, acoustics and electromagnetism exhibit similar phenomena and are tackled with the same kind of technique. Jones's exhaustive study is unique in providing a unified treatment of the two fields, bringing out their common and disparate features and showing how they cross-fertilize one another. The book is designed so that the reader with a familiarity with either Maxwell's Equations or the equation of sound waves in fluid dynamics can follow the developments in both fields without difficulty. This is a comprehensive treatment which will provide a needed reference for researchers in applied mathematics and mathematical physics but also caters to the student, who is taken up to the frontiers of research with the help of appropriate exercises. Engineers with any sort of mathematical competence, particularly electrical engineers and those concerned with communications technology, will need to have access to it.
Keywords: Physics; Electricity; Acoustics